DAMPAK GAME ONLINE TERHADAP PERILAKU SOSIAL SISWA SMPN 1 PUNCAK SORIK MARAPI: SEBUAH ANALISIS FENOMENOLOGIS [IMPACT OF ONLINE GAMES ON SOCIAL BEHAVIOR OF SMPN 1 PUNCAK SORIK MARAPI STUDENTS: A PHENOMENOLOGICAL ANALYSIS] - Muhammad Amin Nasution; Muhammad Rizal Januri; Marwan Ali Shodikin (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2022)
Adolescence is a period of transition between children and adults, at this time teenagers are also known as periods of difficulty. The current era of technology has received a lot of attention from the wider community, one of which is the problem of online games. This research is motivated by the existence of very rapid technological developments that cause students to experience changes in social behavior. The basic purpose of this study is to explain the positive and negative impacts of online games on the social behavior of students at SMP Negeri 1 Puncak Sorik Marapi. The research method used is a qualitative method. The approach used by the researcher is a phenomenological approach. This study will focus on the impact of online games on students' social behavior. The results of this study are the negative impact of students who are considered addicted to online games, of course, very diverse including students sometimes speak impolite and polite, some students also forget time for school because of the fun of playing, students also often spend time playing games at school, stealing time. during study hours so that it has an impact on social change which often forgets the surrounding environment, while the positive impact of online games on the social behavior of SMP Negeri 1 Puncak Sorik Marapi students is in the form of adding relationships, means of refreshing, collaborating, and students can express their emotions through playing online games.